2016
DOI: 10.3126/repos.v1i0.16040
|View full text |Cite
|
Sign up to set email alerts
|

Insureds’ Perception towards Insurance Services in Pokhara

Abstract: The basic objective of this study is to analyze the perception or opinion of Insured on the services provided by the insurers, agents and surveyors in Pokhara valley. Study shows 71.57 percent respondents agreed insurance creates awareness among people. Similarly, 73.53 percent respondents agreed it also provides social security. Regarding interest rates on loan, 57.43 percent respondents are indifferent on their opinion that whether the rate of interest on loan is cheaper or not but 30.69 percent are agreed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The majority (67.1%) of our respondents strongly agreed that the health insurance policy scheme is necessary. Similarly, a study from Pokhara, Nepal found that 61.0% of the respondents had a positive perception on its necessity [19]. These findings are also consistent with the study conducted in Dhaka, Bangladesh [20].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The majority (67.1%) of our respondents strongly agreed that the health insurance policy scheme is necessary. Similarly, a study from Pokhara, Nepal found that 61.0% of the respondents had a positive perception on its necessity [19]. These findings are also consistent with the study conducted in Dhaka, Bangladesh [20].…”
Section: Discussionsupporting
confidence: 83%
“…The statement that health insurance policy has wide risk coverage and could be a means of financial security was agreed by the majority of respondents. Other reports have stated that wide risk coverage was also the major factor for taking up health insurance policy scheme [18,19]. The majority (67.1%) of our respondents strongly agreed that the health insurance policy scheme is necessary.…”
Section: Discussionmentioning
confidence: 55%
“…Several surveys have been devoted both in Nigeria and other countries of the world to identify claims handling processes in insurance and how they are in relations to policyholders' perception in motor insurance (e.g. Bortoluzzo, Claro, Caeteno, & Artes, 2011;Gangil & Vishnoi, 2020;Gurung, 2016;Islam & Hossain, 2018;Yusuf & Ajemunigbohun, 2015).…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…People; especially the policy-holders or insured are the main party of insurance. So, the insurers should give due importance to the policy-holders while discharging their services (Gurung, 2016). With the growing awareness among the people about insurance, various services provided by the companies and availability of insurance facilities across the globe, the insurance sector is emerging very rapidly and there is a need to identify the main factors that affect the customer's demand for life insurance.…”
Section: ~Nepalese Journal Of Insurance and Social Securitymentioning
confidence: 99%